PENGEMBANGAN MEDIA INTERAKTIF BERBASIS ANDORID (MY KITABAH) PADA MAHARAH KITABAH DI SMP IT MUTIARA HATI SEMARANG: DEVELOPMENT OF ANDROID-BASED INTERACTIVE MEDIA (MY KITABAH) AT MAHARAT KITABAH AT JUNIOR HIGH SCHOOL MUTIARA HATI SEMARANG - Fatikhasari, Saila Rachma; Irawati, Retno Purnama (Lisanul Arab: Journal of Arabic Learning and Teaching, 2024)
The research that developed android-based interactive learning media in Arabic language learning in maharah kitabah aims to analyze the needs of students and teachers in the development of interactive media, describe the development of prototypes in the developed media, analyze the feasibility of the developed interactive media and the responses of students and teachers to the developed media. Methods used in this study is Research and Development (RnD) with the development model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The types of data taken in this study are quantitative data and qualitative data.  Quantitative data analysis techniques are in the form of analysis of feasibility test data by experts, analysis of student responses. Meanwhile, qualitative data analysis techniques are in the form of source triangulation and technique triangulation. The results of problem analysis, media analysis, and analysis of student and teacher needs show that media development is needed with 98% approval from students and teachers. The results of the media feasibility test by the validators of media experts and material experts received an average score of 3.49 from media experts with the "feasible" category and an average score of 3.47 from material experts with the "feasible" category to be used in the learning process. The analysis of student and teacher responses is very helpful in the development of the My Kitabah application.